Overcoming barriers to intercultural communication - Cook, Roger, 1944-; Stowell, Jessica; Educational Video Group (Greenwood, IN : Educational Video Group, 2005)
This video emphasizes the importance of communication between cultures in the 21st century. The discussion analyzes barriers such as: ethnocentrism, anxiety and prejudices. The viewers are suggested to see ways to break down these barriers and increase the ease of communication in today's world community.
Edited by Diane Lindley, Harold Rogers.
Featuring, Jessica Stowell.
DVD.
English
Keywords: Intercultural communication; Interpersonal communication